Subject of Witness Testimony During Interrogation (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In criminal proceedings, witness testimony serves as a central means of establishing factual circumstances. According to the Criminal Procedure Code of the Republic of Uzbekistan, a witness is legally obliged not only to testify but to provide truthful information. This responsibility has implications both for the reliability of evidence and the procedural integrity of criminal trials. Despite the formal legal framing, ambiguity remains regarding the scope and interpretation of a witness's obligation to testify truthfully and the admissibility of information based on its origin and reliability. This study aims to analyze the subject of witness testimony during interrogation, including the legal basis, procedural mechanisms, and evidentiary value, by examining both domestic and foreign legislation. The findings indicate that while the law obligates witnesses to provide information known to them, only deliberately false testimony constitutes a criminal offense. Furthermore, the personal attributes and perceptions of the witness significantly affect the evidentiary value of their statements. The article contributes a comparative perspective by integrating international legal approaches and scholarly interpretations into the analysis of Uzbekistan’s legal framework. These insights underline the importance of refining interrogation practices to assess the reliability of testimony and ensuring procedural fairness by balancing the rights of both prosecution and defense during witness examination.